2011
DOI: 10.1063/1.3665391
|View full text |Cite
|
Sign up to set email alerts
|

Computing the energy of a water molecule using multideterminants: A simple, efficient algorithm

Abstract: Quantum Monte Carlo (QMC) methods such as variational Monte Carlo and fixed node diffusion Monte Carlo depend heavily on the quality of the trial wave function. Although Slater-Jastrow wave functions are the most commonly used variational ansatz in electronic structure, more sophisticated wave functions are critical to ascertaining new physics. One such wave function is the multi-Slater-Jastrow wave function which consists of a Jastrow function multiplied by the sum of Slater determinants. In this paper we des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 19 publications
2
111
0
1
Order By: Relevance
“…To enhance prefetching the algorithm should allow the predictability of the data arrival in the CPU (that is, avoid random access as much as possible). It is this important aspect that has motivated us to use Sherman-Morrison updates, despite the fact that a method like the Table method [81] has formally a better scaling. Indeed, massive calculations of scalar products at the heart of repeated uses of SM updates are so ideally adapted to present-day processors that very high performances can be obtained.…”
Section: Evaluating Very Large Number Of Determinants In Qmcmentioning
confidence: 99%
See 3 more Smart Citations
“…To enhance prefetching the algorithm should allow the predictability of the data arrival in the CPU (that is, avoid random access as much as possible). It is this important aspect that has motivated us to use Sherman-Morrison updates, despite the fact that a method like the Table method [81] has formally a better scaling. Indeed, massive calculations of scalar products at the heart of repeated uses of SM updates are so ideally adapted to present-day processors that very high performances can be obtained.…”
Section: Evaluating Very Large Number Of Determinants In Qmcmentioning
confidence: 99%
“…Indeed, computing at each of Monte Carlo step the first and second derivatives of the trial wavefunction (drift vector and local energy) is the hot spot of DMC. However, efficient algorithms have been proposed to perform such calculations [80][81][82]. Here, we have briefly summarized our recently introduced algorithm allowing to compute N -determinant expansions issued from selected CI calculations with a computational cost roughly proportional to √ N (with a small prefactor).…”
Section: Summary and Some Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13] However, unlike the electronnuclear cusp, atom-centered basis functions are not ideal for accurate description of the many-electron wavefunction near the electron-electron cusp. [14][15][16] Indeed it * corresponding author: archakra@syr.edu has been shown that the slow convergence of a full configuration interaction (FCI) calculation with respect to the one-particle basis is related to the inadequate treatment of the electron-electron cusp. [15] The solution is to include explicit r 12 dependence in the form of the wavefunction, and there is a large assortment of quantum chemical methods that have incorporated this approach.…”
Section: Introductionmentioning
confidence: 99%